Kotsipak M. Structural and semantic features of phraseological units - Kotsipak M. (Philological Treatises, 2020)
The article considers structural and semantic features of phraseological units, in the American detective genre of the XXI century their nature and functions. Attention is being focused upon the lexico-semantic system jf the English language as a means of cognition and communication.